The proteomics of lipid droplets: structure, dynamics, and functions of the organelle conserved from bacteria to humans - Yang, Li (The American Society for Biochemistry and Molecular Biology, 2012)
Lipid droplets are cellular organelles that consists of a neutral lipid core covered by a monolayer of phospholipids and many proteins. They are thought to function in the storage, transport, and metabolism of lipids, in signaling, and as a specialized microenvironment for metabolism in most types of cells from prokaryotic to eukaryotic organisms. Lipid droplets have received a lot of attention in the last 10 years as they are linked to the progression of many metabolic diseases and hold great potential for the development of neutral lipid-derived products, such as biofuels, food supplements, hormones, and medicines. Proteomic analysis of lipid droplets has yielded a comprehensive catalog of lipid droplet proteins, shedding light on the function of this organelle and providing evidence that its function is conserved from bacteria to man. This review summarizes many of the proteomic studies on lipid droplets from a wide range of organisms, providing an evolutionary perspective on this organelle.